Use of Steel Slag as Coarse Aggregate for the Production of Pervious Concrete - Georgia Vardaka; Kiriakos Thomaidis; Christos Leptokaridis; Stamatis Tsimas (Journal of Sustainable Development of Energy, Water and Environment Systems, 2014)

(untitled)
Pervious concrete is a type of concrete with significantly increased water permeability, ensuring increased rates of drainage of rainfall. The high porosity is achieved by removing a large percentage of fine aggregates from the mix. The present paper is an approach for the addition of steel slag as a substitute for coarse aggregates in pervious concrete. More specifically, three types of aggregates have been used: steel slag, construction and demolition wastes and conventional limestone aggregates. The produced pervious concretes are compared for their properties, such as water permeability, compressive strength and abrasion behaviour. Also this paper contains the study of the porosity analysis of these pervious concrete mix designs by using porosity profiles produced from X-ray CT Scanning. According to the results of this paper, it is observed that the incorporation of industry by-products or of Construction and Demolition (C&D) wastes leads to better abrasion behaviour, and to the increase, in some cases, of the compressive strength and of the water permeability.